THE ROLE OF APPLYING ISLAMIC BRANDING TO PURCHASING DECISIONS - Erlangga Sidiq; Isra Hayati; Fitra Sulistina Wati (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of Islamic branding and religiosity on purchasing decisions for HNI-HPAI Halal Mart BC Medan 8 products. This study used quantitative methods and associative research types. The population in this study were consumers of HNI-HPAI Halal Mart BC Medan 8 and the sample used was 68 people using purposive sampling. Data collection techniques used in this study are questionnaires, interviews and documentation. The method of analysis in this study is a test of data validity and reliability, normality test, classical assumption test, multiple regression test, hypothesis testing, and linear coefficient determination test. The results of the study show that: (1) Islamic Branding has a positive and significant effect on Purchase Decisions. The results of the calculations that have been carried out are the t_count t_table of 2,378 1,997 with a significance value of 0.020 0.05, which indicates that H_0 is rejected and H_1 is accepted. (2) Religiosity has a positive and significant effect on purchasing decisions. The results of calculations that have been carried out value t_count t_table of 5.443 1.997 with a significance value of 0.000 0.05, which indicates that H_0 is rejected and H_2 is accepted. (3) Simultaneously, it is known that Islamic Branding and Religiosity have a significant effect on purchasing decisions for HNI-HPAI Halal Mart BC Medan 8 products with a significance number of F_count F_table (26.583 3.14). (4) Based on the coefficient determination test, it shows that the R-square value is 0.929 or 92.9%, it explains that the independent variables, namely Islamic Branding and Religiosity affect the Purchase Decision of HNI-HPAI Halal Mart BC Medan Products 8. While the remaining 7.1% influenced by variables not examined in this study.